Level of Functioning of Service Quality of a Private Higher Education Institution in the Philippines: Personnel and Student Perspectives - Jojie R. De Ramos; Jesus P. Briones (Education Policy and Development, 2024)
Competitive educational institutions emphasize how service quality influences customer satisfaction. This study investigated the level of service quality functioning of a private higher education institution (HEI) in the Philippines, as assessed by its personnel and students. Employing a mixed research method, data were gathered from 22 full-time personnel and 140 students of the subject HEI by using a survey questionnaire distributed online via Google Forms. Statistical tests, such as weighted mean, standard deviation, and independent t-tests, were employed in the data analysis. The study found that service quality engagement of the institution is at an acceptable level of functioning. However, there is still room for improvements in all service quality dimensions. Moreover, the study disclosed that there were no statistically significant differences between the assessments of personnel and students in terms of service quality. In-person interviews revealed that most issues and challenges in service quality relate to the tangibility, responsiveness, and assurance aspects, where the need for efficient resource allocation, improved communication, and infrastructure enhancements are essential. These findings have given light to propose a comprehensive action plan that will support the institution in improving the current functioning of its service quality. Furthermore, this study can serve as a model for other private HEIs to develop service quality enhancement strategies to better serve their stakeholders.